Expression Strategy of Soluble Recombinant Human TGF-β3 in Escherichia coli: sfGFP -Fusion Tag - Sema Bilgin (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Transforming growth factor-beta 3 (TGF-β3) is an important cytokine involved in various biological processes. TGF-β3 is used as a scar-reducing antifibrotic agent for acute and chronic wounds and fibrosing disorders. TGF-β3, a valuable therapeutic protein, is produced recombinantly in different expression systems. TGF-β3, produced in the Escherichia coli (E. coli) expression system, widely used due to its various advantages in recombinant production, is commercially available. However, the main problem encountered in protein expression in E. coli cells is the formation of an inclusion body. Various approaches have been developed to solve this problem. The use of a fusion tag is one of the most powerful strategies used to obtain protein in the soluble active form in the E. coli expression system. Superfolder GFP (sfGFP) is one of the fusion tags used to increase the solubility of the fusion partner in E. coli. In this study, TGF-β3 with sfGFP fusion tag (sfGFP-TGFβ3) was successfully produced in soluble form in E. coli BL21 (DE3) in high yield and purity for the first time. Purified protein was identified by western blot and SDS-PAGE. 20 mg of protein with 98% purity was obtained from 1 L of bacterial culture. It was determined that the obtained high purity protein did not have a cytotoxic effect on BJ normal human skin fibroblast cells. The impact of sfGFP-TGFβ3 fusion protein on wound healing was evaluated with in vitro scratch wound healing assay. The results showed that the sfGFP-TGFβ3 fusion protein produced in soluble form in the E. coli expression system has the potential to support the wound healing process.